2020
DOI: 10.33808/clinexphealthsci.600151
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Serum C-Reactive Protein and Neutrophil Lymphocyte Ratio According to Thyroid Function Status

Abstract: Objective: We aimed to investigate neutrophil lymphocyte ratio (NLR), leukocyte count (WBC), mean platelet volume (MPV) and C-reactive protein levels (CRP) as inflammatory markers according to thyroid function status in hypo-hyperthyroidism patients.Methods: Data of patients (n=454, age>18) who applied to the Eskisehir Osmangazi University Hospital between March 2018 and December 2018 were evaluated retrospectively. There were 79 patients in hyperthyroidism group (TSH<0.27 µIU/ml, group I), 297 patients in eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Therefore, our study complements the role of NLR and PLR in cerebrovascular diseases and provides new ideas for clinical practice. NLR is considered an emerging marker between the immune system and disease including IS and thyroid function dysfunction [32,33]; the results of our study are a further proof underscoring the involvement of immune system in the pathogenetic chain of IS. A previous study showed inconsistent trends in NLR and CRP levels in patients with COVID-19 [34], whereas our study found that both NLR and CRP levels increased simultaneously in IS-related HHCY patients, This may be due to COVID-19 patients being infected by the novel corona virus.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, our study complements the role of NLR and PLR in cerebrovascular diseases and provides new ideas for clinical practice. NLR is considered an emerging marker between the immune system and disease including IS and thyroid function dysfunction [32,33]; the results of our study are a further proof underscoring the involvement of immune system in the pathogenetic chain of IS. A previous study showed inconsistent trends in NLR and CRP levels in patients with COVID-19 [34], whereas our study found that both NLR and CRP levels increased simultaneously in IS-related HHCY patients, This may be due to COVID-19 patients being infected by the novel corona virus.…”
Section: Discussionsupporting
confidence: 72%
“…A study published by Faith and his colleagues demonstrated a significant difference in TSH levels between hypothyroidism and hyperthyroidism groups [33]. Table (4) 125 shows the statistical relationship between the patients and the healthy groups in TSH levels.…”
Section: 25%mentioning
confidence: 95%
“…There is a widespread perception that increased inflammation in COPD causes a decrease in TSH level by affecting the pituitary gland and also reduces the formation of fT3 from fT4. Kar et al [16] reported a significant negative correlation between CRP and TSH (r = −0:108, p < 0:05), although in a study which included 190 subjects, Lee et al declared that there was no significant relationship between CRP and TSH [17].…”
Section: Pulmonary Medicinementioning
confidence: 96%